Production characteristics of Chios x Akkaraman F1 and B1 crossbred lambs.: II.: Fattening performance, slaughter and carcass characteristics - Esen, F; Özbey, O (Scientific Technical Research Council Turkey, 2001)
This study was carried out to investigate the fattening performance, and slaughter and carcass characteristics of Chios x Akkaraman F-1 and B-1 crossbred lambs. The data for the fattening study were obtained from 8 F-1 and 10 B-1 crossbred lambs. Five male lambs from each genotype were slaughtered to determine the slaughter and carcass characteristics. Lambs were fed with alfalfa hay and concentrates ad libitum in the fattening period. During the fattening period, the average daily live weight gains in crossbred F-1 and B-1 groups were 238.04 g and 232.07 g, and the amount of consumed concentrate feeds for 1 kg live weight gain were 3.95 kg and 3.94 kg. respectively. Cold carcass weights were 18.71 kg and 19.08 kg, carcass dressing percentages were 45.37% and 46.41%, and tail fat percentages were 10.23% and 5.45% (P<0.01) for F-1 and B-1 crossbred groups slaughtered at 40 kg live weight.
Keywords: Akkaraman; Chios; crossbreeding; fattening; carcass